Occurrence of MDR1 1-delta mutation in herding dog breeds in Portugal - Barroso, Maria Cristina; Grilo, Andreia; Aguiar, Sandra; Aires da Silva, Frederico; São Braz, Berta (Frontiers in Veterinary Science, 2022)
The impact of drug transporters in veterinary medicine has been recognized in recent years. One of the most well-characterized is the product of the MDR1 gene, P-gp. A 4-bp deletion in the MDR1 gene known since 2001 has been described to affect herding dog breeds. Since many used drugs in veterinary medicine are substrates for P-gp, including the macrocyclic lactones, such as avermectins, this 4-bp deletion causes a pathological condition known as “ivermectin toxicosis”. For this reason, it is important to determine the animal status concerning this mutation. In Portugal, the information of the occurrence of this mutation in our breeds is limited. The aim of the present study was to determine the occurrence of this mutation and evaluate its association with Portuguese and non-Portuguese dog breeds in Portugal. To achieve this, a total of 105 animals were studied for the presence of the MDR1 4-bp deletion, 23 of which were from Barbado da Terceira, 10 from Cão da Serra d’Aires, 55 belonging to breeds known to carry the mutation (Australian Shepperd, Border Collie and others) and 17 to other breeds (Labrador Retriever, Jack Russel, and others). Despite the small sample size, we observed the presence of the MDR1 1 - delta mutation in previously described breeds and identified this mutation in Barbado da Terceira breed for the first time.